Pengaruh Reputasi Perusahaan, Environmental, Social and Governance dan Kualitas Audit Terhadap Tax Avoidance - Anggraini, Pingkan; Wahyudi, Ickhsanto (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The study examines whether a company reputation with the proxy of top brand index, ESG with ESG reporting guide 2.0 and audit quality by dummy methods affects a tax avoidance either directly or indirectly. This study uses a quantitative method that is explanatory-causality with the aim of explaining and estimating the hypothetical relationship of company reputation, ESG and audit quality and tax avoidance by using a sample collection method based on certain characteristics or criteria or called purposive sampling. Based on 25 LQ45 companies in BEI (the Indonesian Stock Exchange) in 2019 to 2021 through regression to analyze the relationship between the company reputation, audit quality and ESG with a tax avoidance. The purposive sampling is a way of selected samples from this research. Analyzing data using SPSS software. The result have been obtained that a company reputation affects tax avoidance negatively as well as with the audit quality. Beyond that ESG cant’t affect tax avoidance.